Analisis Penerapan Target Costing dalam Upaya Mengoptimalkan Perolehan Laba pada UMKM Melvi’s Cake - Salimah Salimah; Tuti Anggraini; Kusmilawaty Kusmilawaty (Universitas 45 Surabaya, 2024)
Target costing is a cost management planning strategy to reduce costs. This method is done by doing value engineering or eliminating inefficient costs. This study aims to analyze cost management and targeted profit improvement at UMKM Melvi`s Cake, so that it can help UMKM Melvi`s Cake businesses in planning to increase profits. This type of research is qualitative using descriptive analysis. The object of research is UMKM Melvi`s Cake. The data analysis technique used is by analyzing the production process, analyzing product prices with competitors and implementing the target costing method. The results of the study show that the Melvi`s Cake MSME business can increase profits by applying the target costing method. The application of target costing is carried out through a value engineering process consisting of the stages of purchasing eggs from one supplier and buying from another, purchasing a cheaper quantity of flour, and reducing packaging costs. Through this process, the company saved costs of Rp. 1,744,000 which previously amounted to Rp. 1,935,000. for the production of celebration cakes or Party Cake every day. With these savings, Melvi`s Cake MSME was able to optimize the desired sales profit by 31%, from previously only being able to get a sales profit of 29%.